PEDAGOGICAL FEATURES OF PRACTICAL PHYSICAL TRAINING OF STUDENTS OF THE ACADEMIC LYCEUM OF THE MINISTRY OF INTERNAL AFFAIRS OF THE REPUBLIC OF UZBEKISTAN - Ismailov Alisher Ulugbekovich (American Journals, 2023)
This article describes in detail the practical physical training of academic high school students.
Keywords: Military power, spiritual force, border, powerful, training.